Michelle Cliff s Abeng and No telephone to heaven: a call to resistance - Domingues, Teresa Barreto (2012)
Postcolonial writers have been engaged in exposing the painful legacies of slavery and colonialism, through the reclaiming of histories that have been appropriated and distorted by master narratives. The investigation and retelling of the lost past of former colonies has been a strategy used to reconstruct identities fragmented as a result of the multiple oppressions that authors have suffered or witnessed. Michelle Cliff is a diasporic Jamaican-born novelist, poet, and essayist who lives in the United States. She is one of the many postcolonial voices committed to a literature of resistance that struggles for cultural decolonization and encourages the feeling of belonging. The aim of this dissertation is to analyze Cliff s semi-autobiographical novels, Abeng (1984) and No Telephone to Heaven (1987) that deal with matters related to colonial and post-colonial practices. The two novels portray the saga of the protagonist Clare Savage, through which Cliff reveals the impact of colonization on the Caribbean, exposes the configurations of power deriving from the intertwining of race, class, and gender, and criticizes the misrepresentation of Jamaica s history, which is disseminated through the colonial education Jamaicans have been subjected to. The author also explores the effects diasporas have on the process of identity construction and the movement from diasporic subjects to rescue and recreate a history of their own